Pengaruh Laba dan Struktur Modal Terhadap Nilai Perusahaan dengan Dividen sebagai Pemoderasi - Maeka Sella Agustina; Ahmad Yani; Rike Selviasari (Jurnal Proaksi, 2025)
Main Purpose – This study aims to analyze the effect of earnings and capital structure on firm value with dividends as a moderating variable. Method – This study employs a quantitative approach using secondary data from the financial statements of consumer goods subsector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. A purposive sample of 29 companies (116 observations) was analyzed using multiple linear regression and moderated regression analysis (MRA) with IBM SPSS 25. Main Findings –The results show that earnings proxied by ROE and EPS as well as capital structure proxied by DER have a significant positive effect on firm value, while ROA and DAR have no effect. Dividends proxied by the Dividend Payout Ratio (DPR) moderate the effect of ROE, EPS, and DAR on firm value, whereas dividends proxied by the Dividend per Share (DPS) do not moderate the effect of EPS, DAR, and DER Theory and Practical Implications - This study extends signaling theory by demonstrating the dual role of dividends, both in strengthening fundamental information and in concealing performance weaknesses. Practically, companies should align their dividend policies with earnings and capital structure to maintain investor trust and enhance firm value. Novelty –In contrast to earlier research, this study offers a more varied set of measurements by introducing dividends as a moderating variable proxied by DPR and DPS in the relationship between earning and capital structure on firm value. Earnings are measured by ROA, ROE, and EPS, while capital structure is measured by DAR and DER. Keywords:profit, capital structure, dividends, firm value